2014
DOI: 10.20870/jph.2014.e004
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Air-Seeding: Watching the Formation of Embolism in Conifer Xylem

Abstract: Water transport in plants is based on a metastable system as the xylem "works" at negative water potentials (ψ). At critically low ψ, water columns can break and cause embolism. According to the air-seeding hypothesis, this occurs by air entry via the pits. We studied the formation of embolism in dehydrating xylem sections of Juniperus virginiana (Cupressaceae), which were monitored microscopically and via ultrasonic emission analyses. After replacement of water by air in outer tracheid layers, a complex movem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Tyloses that are formed in vessels in the absence of local bacteria could also be caused by air embolisms formed as a result of pathogen‐derived cavitation in the xylem. During drought, reduced water uptake and increased transpiration lower xylem pressure to a point where air is pulled into a water‐filled vessel from adjacent air‐filled spaces, causing the water column to break (resulting in an air embolism) (Hopkins, 1989; Mayr et al, 2014). McElrone et al (2008) found that petioles of X. fastidiosa ‐infected oak trees exhibited increased embolism prior to hydraulic failure when vessel occlusion occurred with the onset of scorch symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Tyloses that are formed in vessels in the absence of local bacteria could also be caused by air embolisms formed as a result of pathogen‐derived cavitation in the xylem. During drought, reduced water uptake and increased transpiration lower xylem pressure to a point where air is pulled into a water‐filled vessel from adjacent air‐filled spaces, causing the water column to break (resulting in an air embolism) (Hopkins, 1989; Mayr et al, 2014). McElrone et al (2008) found that petioles of X. fastidiosa ‐infected oak trees exhibited increased embolism prior to hydraulic failure when vessel occlusion occurred with the onset of scorch symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…In moist soils, these pressures are moderate, typically above 22 MPa, but during drought, they decrease considerably, as plants are forced to extract water from drying soil, which reduces the stability of the water column. Below a specific pressure threshold, cavitation events occur when airwater menisci located at pores between xylem conduits break (Tyree, 1997;Cochard et al, 2009;Mayr et al, 2014), vaporizing sap, reducing xylem conductance, and eventually leading to plant death by desiccation (Brodribb et al, 2010;Urli et al, 2013). The xylem pressure at which cavitation occurs, leading to 50% loss of hydraulic function (P 50 ), is a trait that varies widely across species (Delzon et al, 2010;Bouche et al, 2014) and links with climate: xeric species are more resistant to cavitation than species that occupy more mesic habitats (Brodribb and Hill, 1999;Maherali et al, 2004;Choat et al, 2012;Pittermann et al, 2012).…”
mentioning
confidence: 99%
“…Xylem sap transported within the interconnected system of dead tracheary elements under negative pressure (tension) is prone to cavitation [ 105 ], which can be induced by air seeding and leads to bubble formation when air passes through the pores of the pit membranes [ 106 , 107 , 108 ]. Cavitation can also be induced by air bubbles adhered to the cracks in the walls of dead elements [ 109 , 110 , 111 ].…”
Section: Regulation Of Xylem Hydraulic Conductivity By the Xylem Parenchymamentioning
confidence: 99%